The Sustainability Of The "Refuse Of Bal" Ceremony In The Nagari Mandeh Tarusan Fisherman Community, Pesisir Selatan District (Perspectiveclifford Geertz's Symbolic Interpretative) - Karlina, Mutiara (LANGGAM: International Journal of Social Science Education, Art and Culture, 2024)
This research is motivated by the implementation of the tradition of rejecting reinforcements in the Nagari Mandeh community which is still ongoing in the modern era. In addition, the people of Nagari Mandeh also believe that the empty chart is caused by the many "ubili" or evil spirits that come to the Nagari Mandeh area so that the implementation of the ceremony of rejecting reinforcements is the only (preventive) solution so that the catastrophe that occurs in their area can go away. The purpose of this study is to reveal the factors that influence the ceremony of rejecting reinforcements in the fishing community of Nagari Mandeh Tarusan, Pesisir Selatan Regency. This research is a descriptive qualitative research with data collection methods in this study carried out by non-participant observation. Data were collected by observation, interview and document study techniques.In analyzing the factors that influence the ceremony of rejecting reinforcements in the fishing community of Nagari Mandeh, the researcher uses symbolic interpretive theory. The results of this study indicate that the factors that influence the resilience of repelling reinforcements can be seen from the cultural factors of the coastal community's economy and education. These two factors influence each other so that the tradition of the ceremony of rejecting reinforcements in the Nagari Mandeh community is still maintained today even though it is in the modern era. The ceremony of rejecting reinforcements in Nagari Mandeh was carried out for three consecutive days